Vadba Gyrotonic – sodobna alternativa telesni pripravi plesalcev - Šifrar, Tina (Šport (Ljubljana), 2024)
Physical, technical, and choreographic demands require dancers to have good physical fitness. The Gyrotonic Expansion System® method is an innovative and unique training approach that enables dancers to enhance their physical fitness through movement patterns similar to dance movements. It is used to improve flexibility, coordination, balance, and posture, strengthen the muscles of the legs, arms, and torso, gain better control over movements, and with the aim of relaxation and better well-being. The exercises are designed so that each movement flows smoothly into the next, allowing the body to move without abrupt motions. These precisely designed movement sequences help dancers improve their performance and prevent injuries. The training system uses specialized equipment that guides, assists, and challenges individuals, helping them to enhance their psychophysical abilities.
Keywords: dance; Gyrotonic; physical conditioning; physical fitness; ples; sport; šport; telesna priprava; telesna zmogljivost